Analisis Faktor-Faktor yang Memengaruhi Pembiayaan Bank Syariah untuk Sektor Pertanian di Indonesia - Irfan Syauqi Beik; Winda Nur Aprianti (Jurnal Agro Ekonomi, 2013)
EnglishIndonesia’s agricultural sector deals with limited financial access. Hence, Islamic banks can play a significant role in providing financial resources for national agricultural development. This paper attempts to analyze determinants of agricultural financing in the Islamic banking industry. It utilizes monthly data of Islamic banking industry from July 2004 until December 2010. It employs VAR/VECM as its analytical method. The findings show that bonus of Islamic ‘Bank Indonesia’ certificate (SBIS), conventional rate of Bank Indonesia (SBI) certificate, equivalent rate of financing, and equivalent rate of return on deposit (third party fund) positively significantly affect agricultural financing in the long run. However, the number of deposit (third party fund) and conventional bank interest rate are negatively related with agriculture financing. In addition, inflation and non-performing financing are not affecting agriculture financing neither in the short run nor in the long run. This paper suggests the increase in agricultural financing proportion for agriculture should be in accordance with the increase in total deposit value. It also recommends improvement of the human resources competency in agriculture sector as well as strengthening instruments of Islamic monetary policy. IndonesianSalah satu problematika utama yang dihadapi oleh sektor pertanian di Indonesia adalah keterbatasan akses finansial. Sehingga, perbankan syariah dapat memainkan peran yang signifikan dalam menyediakan pembiayaan bagi pembangunan pertanian nasional. Makalah ini mencoba untuk menganalisis faktor-faktor yang memengaruhi pembiayaan pertanian pada perbankan syariah. Statistik bulanan industri perbankan syariah mulai Juli 2004 hingga Desember 2010 digunakan sebagai sumber data, dan metode VAR/VECM digunakan sebagai alat analisis. Hasil penelitian menunjukkan bahwa bonus Sertifikat Bank Indonesia Syariah (SBIS), bunga Sertifikat Bank Indonesia (SBI), equivalent rate pembiayaan syariah dan equivalent rate dana pihak ketiga memengaruhi pembiayaan pertanian pada jangka panjang secara positif dan signifikan. Sedangkan jumlah dana pihak ketiga dan suku bunga bank konvensional memengaruhi pembiayaan pertanian secara negatif. Selanjutnya, inflasi dan Non Performing Financing (NPF) tidak memengaruhi pembiayaan pertanian, baik pada jangka pendek maupun jangka panjang. Penelitian ini merekomendasikan peningkatan proporsi pembiayaan pertanian seiring dengan peningkatan jumlah dana pihak ketiga, peningkatan kompetensi SDM perbankan syariah yang menguasai sektor pertanian, dan penguatan instrumen kebijakan moneter syariah.